The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1016/j.jsv.2012.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Determining correlation and coherence lengths in turbulent boundary layer flight data

Abstract: a b s t r a c tWall pressure data acquired during flight tests at several flight conditions are analysed and the correlation and coherence lengths of the data reported. It is found that the correlation and coherence lengths are influenced by the origin of the structure producing the pressure and the frequency bandwidth over which the analyses are performed. It is shown how the frequency bandwidth biases the correlation length and how the convection of the pressure field might reduce the coherence measured betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 21 publications
7
61
0
Order By: Relevance
“…It was based on the displacement thickness of the boundary layer * . One can also mention a similar attempt made by Palumbo 40 that adjusted the model proposed by Efimsov 41 to experimental data measured on a Gulfstream aircraft fuselage, but here the data is applicable to very high Reynolds number of 2-4.10 7 i.e. about 50 times greater than that of the present study, and the application to the CROR case may be questionable.…”
Section: A Trailing Edge Noisementioning
confidence: 62%
“…It was based on the displacement thickness of the boundary layer * . One can also mention a similar attempt made by Palumbo 40 that adjusted the model proposed by Efimsov 41 to experimental data measured on a Gulfstream aircraft fuselage, but here the data is applicable to very high Reynolds number of 2-4.10 7 i.e. about 50 times greater than that of the present study, and the application to the CROR case may be questionable.…”
Section: A Trailing Edge Noisementioning
confidence: 62%
“…Additional sensors spaced at 6 mm, 12 mm and 36 mm were added to increase the length of the arrays beyond the point of expected significant correlation. Detailed information about the flight test data, test bed instrumentation, data consistency and analysis are described in [10,29]. Flight tests measurements were acquired at three different flight conditions, as shown in Table 1, which will be referred to as Cases 1, 2 and 3 throughout this paper.…”
Section: Flight Tests Data Versus Predicted Datamentioning
confidence: 99%
“…The objective is to compare the experimental data with the empirical results in order to establish a quantitative analysis on the produced plate radiated sound power (RSP). The experimental data for the present study were acquired in a flight test that was a cooperative work between the Gulfstream Aerospace Corporation, Boeing Commercial Airplanes and the National Aeronautics and Space Administration (NASA) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The reference power spectrum and coherence length are predicted using Efimtsov's models which, in turn, depend on flight conditions. The results of a recent flight test 10 indicated that the measured wall pressure varied over short distances, at some locations agreeing with predictions, at others substantially deviating from predictions. This kind of spatial variability has been observed before 11 and had been attributed to differences in the flushness of the sensors 12 .…”
Section: Introductionmentioning
confidence: 65%
“…Gulfstream, Boeing and NASA conducted a cooperative flight test to acquire wall pressure data in an effort to validate and/or advance the models in use by the respective organizations 10 . The data were acquired from sensors mounted in a window blank installed in the forward window area of a G550 aircraft, Fig.…”
Section: Athe Flight Testmentioning
confidence: 99%